2021
DOI: 10.7759/cureus.14836
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence Among Healthcare Workers in a Tertiary Medical City in Riyadh: A Cross-Sectional Study

Abstract: IntroductionWorkplace violence is a common problem that is encountered by healthcare workers worldwide; however, it is still under-studied in Saudi Arabia. This study aims to determine the prevalence of workplace violence and to explore reasons for not reporting it among healthcare workers in a tertiary medical city in Riyadh. MethodsThis cross-sectional study was conducted among 404 healthcare workers who had direct contact with patients or their relatives in a tertiary care medical city in Riyadh, Saudi Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
4
14
0
1
Order By: Relevance
“…The low WPV reporting rate found in the current study is in agreement with the local,[ 24 , 33 , 52 ] regional (20%–42.7%),[ 19 , 20 , 23 ] and international WPV reporting rates (7.9%–35%). [ 15 , 17 , 53 ] Similar to the literature, the participants’ reluctance to report WPV was based on their belief that reporting was useless,[ 8 , 24 , 33 ] reporting was not important,[ 20 , 23 , 49 ] and the fear of negative consequences of reporting.…”
Section: Discussionsupporting
confidence: 90%
“…The low WPV reporting rate found in the current study is in agreement with the local,[ 24 , 33 , 52 ] regional (20%–42.7%),[ 19 , 20 , 23 ] and international WPV reporting rates (7.9%–35%). [ 15 , 17 , 53 ] Similar to the literature, the participants’ reluctance to report WPV was based on their belief that reporting was useless,[ 8 , 24 , 33 ] reporting was not important,[ 20 , 23 , 49 ] and the fear of negative consequences of reporting.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, some victims (preys) ended up with severe depression, several recounted incidents of suicides and some reported nurses being killed, especially in the psychiatric wards in certain hospitals, due to the suspension of specific treatments like mental disorder treatments and psychological counselling services. Moreover, conflicts between patients and clinicians may arise when these mental health services and practices are disrupted (Alharbi et al, 2021; Xie et al, 2021). As a result, registered nurses and other health care professionals must be protected from these perilous undertakings because their service industries are life‐threatening, predominantly during pandemic crises.…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with the risk management unit of the institution, nurse managers should work hand in hand in devising tools for assessing and evaluating workplace violence. Thus, all employees must know about the reporting system and follow up on violence cases because most cases are unreported (Alharbi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…[6] Locally, the percentage of physical WPV ranged from 5% to 67.6%; these vast differences between the findings could be attributed to the focus of those studies on a single city, some hospitals, and specialties or departments with higher risks to encounter violence. [7][8][9][10][11][12] Although limited studies were conducted recently in Kingdom of Saudi Arabia, none was found to explain violence to healthcare workers (HCWs) in various circumstances, combine all workers in different settings, and explore some terminal cities regarding the exposure of their HCWs to violence. [7][8][9][10][11][12][13][14] Physical attacks can cause psychological and bodily injuries to the victims that may range from minor to serious harm, leading to reduced workdays.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Although limited studies were conducted recently in Kingdom of Saudi Arabia, none was found to explain violence to healthcare workers (HCWs) in various circumstances, combine all workers in different settings, and explore some terminal cities regarding the exposure of their HCWs to violence. [7][8][9][10][11][12][13][14] Physical attacks can cause psychological and bodily injuries to the victims that may range from minor to serious harm, leading to reduced workdays. [15][16][17] Recently, WPV has gained attention; however, the low reporting rate remains a problem.…”
Section: Introductionmentioning
confidence: 99%